2015
DOI: 10.2507/ijsimm14(3)1.280
|View full text |Cite
|
Sign up to set email alerts
|

Fixture Layout Design Based on a Single-Surface Clamping with Local Deformation

Abstract: Proposed in this paper is a novel approach to fixture layout design. The contact interface between workpiece and fixture is reduced to a single workpiece surface. This allows reliable machining of the remaining five workpiece surfaces in a single setup. Workpiece clamping is performed by inserting special elements into prepared auxiliary openings on the workpiece. Clamping is thus reduced to indenting of sharp clamping element tips into the workpiece surface. Shallow indenting is performed on surfaces which ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Final machining of the axle pin should be performed in a machine shop equipped with a force vs. displacement controller M. Cvetić, N. Gubeljak Determination of Stresses in the Axle Pin Based on the Wind Model in the Wind Turbine system [29]. The axle pin as the most vital part of the wind turbine should be machined by applying a low feed and depth of cut, as reported in [30], in order to ensure low roughness of the machined surface. The best surface quality was achieved when the axle pin was fixed as a rigid body in the machining centre, as reported in [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Final machining of the axle pin should be performed in a machine shop equipped with a force vs. displacement controller M. Cvetić, N. Gubeljak Determination of Stresses in the Axle Pin Based on the Wind Model in the Wind Turbine system [29]. The axle pin as the most vital part of the wind turbine should be machined by applying a low feed and depth of cut, as reported in [30], in order to ensure low roughness of the machined surface. The best surface quality was achieved when the axle pin was fixed as a rigid body in the machining centre, as reported in [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 16 Finite elements, the ten node tetrahedron [27] Degrees of freedom of the tetrahedral finite element can be described by: 30 are approximation coefficients of the finite element. With the introduction of the coordinates' position of the node and corresponding displacements, the coefficients can be expressed by displacements in the nodes, which are obtained in SolidWorks.…”
Section: Determination Of Bearing Loadmentioning
confidence: 99%
“…A full 3D finite element model (FEM) was used to obtain the displacement, strain, and stress fields of the axle pin. 18 Finite element analysis has been performed by using the FE code ABAQUS. 19 Figure 6 shows the FEM used and the according to the Germanische Lloyd.…”
Section: Numerical Stress Analysismentioning
confidence: 99%
“…Tadich et al [37] considered clamping the workpieces with complex geometry by using tapered wedges that allowed carrying out the parts machining from the five sides with one side locating. The results showed that stiffness of the system "fixture -workpiece" is insufficient for this locating method.…”
Section: Literature Reviewmentioning
confidence: 99%